PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA DIORAMA UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR IPA KELAS III SEKOLAH DASAR - Iin Inayah; Khoimatun; Dadang Suhada (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve learning motivation and learning outcomes by applying the Problem Based Learning (PBL) model assisted by Diorama Media to improve motivation and science learning outcomes for grade III students of UPTD SDN 1 Kedokanbunder Wetan. This type of research is Classroom Action Research (CAR). This research was conducted through three cycles, each consisting of Planning, Implementation, Observation, and Reflection, with research subjects being third-grade students of UPTD SDN 1 Kedokanbunder Wetan, Kedokanbunder District, Indramayu Regency. With a total of 40 students, data collection methods used were questionnaires, tests, and observations. Observations of the application of the problem based learning (PBL) model in cycle I reached 83%, observations in cycle II reached 85%, and observations in cycle III reached 87%. Students' learning motivation in cycle I reached 79%, in cycle II 82%, and in cycle III 85%. Analysis of students' learning outcomes after the action in cycle I showed an average score of 62%, after the action in cycle II the average score was 75%, after the action in cycle III the average score was 85%. Based on these results, it can be concluded that the application of the problem based learning (PBL) model assisted by diorama media can improve learning motivation and science learning outcomes for grade III students of UPTD SDN 1 Kedokanbunder Wetan.